ASSISTANCE AND UTILIZATION OF THE MARKETPLACE IN THE FACEBOOK APPLICATION AS A MEAN OF BUYING BY TRADERS IN PALANGKA RAYA CITY - Akbar, Wahyu; Kurniawan, Rahmad; Tarantang, Jefry; Sodiq; Cornelia, Riska (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Social media is a forum that is familiar to the ears of the Indonesian people, especially in the process of using it to reach the general public in accessing basic needs and supporting the community's economy. As we know, more than one hundred million Indonesians currently access social media which is then used as a tool to reach the wider community. Of the many types of social media circulating according to data from Suara.com, Indonesians use Facebook more as a tool to support basic needs and the economy, as many as 140 million Indonesians access it, which puts us in second place in the world of people who access Facebook media. The current pandemic condition does not necessarily reduce access to social media, in fact, according to the data we found, access to the use of social media has increased, especially in supporting the community's economy. Of the many Facebook users who later attracted our attention to research and explore what later became the attraction of this application in the economic sector. The research that we do is field research (qualitative) with descriptive analysis method and service learning approach in order to obtain data according to the existing facts from the use of the media.